2016
DOI: 10.1007/s11368-016-1453-y
|View full text |Cite
|
Sign up to set email alerts
|

Amendment of sulfate with Se into soils further reduces methylmercury accumulation in rice

Abstract: Purpose Both selenium (Se) and sulfate could largely affect methylmercury (MeHg) dynamics and phytoavailability in soil-rice systems, while their combined effects are less understood. Here, we aimed at exploring the potential effects of sulfate on MeHg accumulation in rice in the presence of Se. Materials and methods Rice was cultivated in inorganic Hgspiked soils amended with Se only (selenite/selenate, BSe treatments^) or Se and sulfate (BSe + Sulfate treatments^). Soil parameters (e.g., pH and redox potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Meta-analysis showed that both Se(VI) and Se(IV) can significantly reduce Hg concentration in plants ( Figure 4 ), which is consistent with most research results ( Wang et al., 2016a ; Wang et al., 2016b ; Wang et al., 2016c ; Tang et al., 2017 ). In addition, meta-analysis also showed that Se(VI) application can reduce the concentrations of Hg more than Se(IV) in plants ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 88%
“…Meta-analysis showed that both Se(VI) and Se(IV) can significantly reduce Hg concentration in plants ( Figure 4 ), which is consistent with most research results ( Wang et al., 2016a ; Wang et al., 2016b ; Wang et al., 2016c ; Tang et al., 2017 ). In addition, meta-analysis also showed that Se(VI) application can reduce the concentrations of Hg more than Se(IV) in plants ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, such methods have limited application to productive agricultural soil due to high cost, and the degradation of soil physical, chemical, and biological properties that can result from remediation . Recent studies have shown that immobilization is a better approach to manage the risk of bioavailable Hg in paddy soil. Selenium compounds, , elemental sulfur, and sulfate have been shown to immobilize Hg when used as a soil amendment although their application beyond laboratory scale is limited. The lack of any proven, reliable, and high-efficiency immobilization technology remains a key barrier for the use of such technology to manage the risk of Hg in productive farmlands.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, S-regulated Hg transformation in agricultural fields (e.g., paddy soils) requires more attention. To date, limited studies have examined S input-influenced Hg transformation in paddy soils, with both promotion and inhibition of Hg II methylation reported. Most of these studies were based on bulk Hg concentration measurements, with little investigation of the precise transformation processes of Hg. Moreover, S species with different valent states determine the redox cycling of S and, thus, influence Hg transformation .…”
Section: Introductionmentioning
confidence: 99%